Evaluation of site effects on forest productivity of planted Khaya ivorensis A. chev. and Hopea odorata roxb. on degraded forestland in Segamat, Johor, Malaysia. - H. I. S. Gandamihardja, Yetti Heryati (2011)
Tropical rainforests play an important role in ameliorating and maintaining global climate. Despite increasing recognition of their importance in the tropics, the amount of natural forests continues to decrease at an alarming rate, mainly due to rapid and extensive forest harvesting that damages soil and vegetation, concomitantly contributing to the degradation of forestland. In Segamat, Johor, Malaysia, there has been an effort by forestry-related local agencies such as the Forest Research Institute of Malaysia (FRIM) to reduce further degradation by rehabilitating forestland through the implementation of forest plantation using high-quality exotic (Khaya ivorensis A. Chev.) and indigenous (Hopea odorata Roxb.) species. In order to evaluate the success of forest rehabilitation or plantation forest, one must understand and assess the abiotic factors of soil in relation to weathering and soil fertility status, as well as biotic factors related to the site suitability of species. However, information on the soil characteristics of degraded forest lands and the suitability of specific exotic and indigenous species to these sites is limited or lacking. The present study of forest plantation of K. ivorensis and H. odorata was conducted five years after planting in degraded forestland in Segamat, Johor. This study is divided into four parts corresponding to the following objectives: (1) to characterize the soils of plantation forest (K. ivorensis and H. odorata) and an adjacent secondary forest, (2) to evaluate the growth performance and biomass accumulation of K. ivorensis in three different soil series, (3) to evaluate the soil fertility status of K. ivorensis in comparison with adjacent secondary forests using the soil fertility index (SFI) and soil evaluation factor (SEF), and (4) to assess the productivity and potential of K. ivorensis and H. odorata for sequestering the source of greenhouse gas CO2. The focus of the first study is characterizing soil properties in terms of morphology, physico-chemical properties, and sesquioxide properties. For this purpose, two soil profiles were dug at each site for plantings of K. ivorensis and H. odorata, as well as in adjacent secondary forests. The soil profiles were described, followed by soil sampling according to soil horizon. The soils were moderately to strongly acidic both in plantation forests and secondary forests. The activity ratios of Al (Alo/Ald) and Fe (Feo/Fed) of the soils at all sites were lower than 0.10, indicating that the soils were undergone to intense weathering and eventually reached the ultimately weathered stage. The point of zero salt effect (PZSE) and the residual charge at PZSE (σp) values at all sites were low, and no clear differences in the profiles were associated with low amounts of Al and Fe oxides and hydroxides. In general, the soil fertility status was low due to intense weathering and the acidic nature of the soils. The second study concerns the growth and biomass accumulation of K. ivorensis at five years old in three soil series (Padang Besar, Rengam, and Durian). At each soil site, three plots with a size of 30 x 40 m were demarcated. The height and diameter of five-year-old K. ivorensis were measured individually, followed by the calculation of survival rate and growth performance in terms of mean annual increment (MAI) in height and diameter. The destructive sampling method was performed at each stand of K. ivorensis where five standing trees were chosen to estimate biomass accumulation. The growth performance of K. ivorensis in terms of MAI in diameter, MAI in height, and basal area was highest at Padang Besar, followed by Durian and Rengam. The best fit regression of an allometric equation using D as an independent variable is recommended for estimating tree component biomass and stem volume at sites. The highest stem volume and biomass accumulation values were recorded at Padang Besar (77.99 m3 h-1 and 63.16 t ha-1, respectively), followed by Durian (53.10 m3 h-1 and 46.33t ha-1, respectively) and Rengam (43.13 m3 h-1 and 40.96 t ha-1, respectively). The third study compares soil fertility status for the Rengam, Padang Besar, and Durian series for K. ivorensis plantation in comparison with adjacent secondary forests by using the SFI and SEF. Soil samples were collected at depths of 0-10 cm (surface soils) and 20-30 cm (subsurface soils) in three replicates for each soil series at both sites. The results showed that soil pH both in planted and secondary forests was moderately acidic to slightly acidic, with low content of exchangeable bases and available P but high Al saturation. The SFI result revealed that the fertility status of Rengam soil was significantly higher than the fertility of the other two soil series, whereas no significant difference was observed in the case of SEF. Based on the SFI and SEF values, there were no significant differences in fertility status between the planted and secondary forests for surface and subsurface soils. In general, planting K. ivorensis on degraded forestland seemed to increase soil fertility status, as was seen in secondary forests. The fourth study assessing the productivity of planted K. ivorensis and H. odorata in terms of growth performance and biomass accumulation is elucidated for a similar soil series (Rengam series). In the Rengam soil series, the growth performance of K. ivorensis in terms of MAID, MAIH, and basal area was higher than that of H. odorata. Similarly, the stem volume of the K. ivorensis stand was 43.13 m3ha-1, significantly higher than H. odorata stands volume of 33.66 m3 ha-1. Nevertheless, the growth performance for H. odorata in this study was higher than in the previous study. K. ivorensis and H. odorata stands have the potential to absorb CO2 from the atmosphere for storage in above ground biomass with values of 15.90 Mg C ha-1 and 13.62 Mg C ha-1, respectively. In addition, the carbon content in the root biomass of the H. odorata stand was higher than that in the K. ivorensis stand, with values of 7.67 Mg C ha-1 and 4.58 Mg C ha-1, respectively. In conclusion, rehabilitating degraded forestland by planting high-quality exotic and indigenous species improves the site quality and productivity of degraded forestland. In addition to the suitability of species to a site, soil fertility in situ should be considered when attempting to rehabilitate degraded forestland in the future.